Quercetin Alleviates Pulmonary Fibrosis in Silicotic Mice by Inhibiting Macrophage Transition and TGF-β-Smad2/3 Pathway - Fei Geng; Lan Zhao; Yuhao Cai; Ying Zhao; Fuyu Jin; Yaqian Li; Tian Li; Xinyu Yang; Shifeng Li; Xuemin Gao; Wenchen Cai; Na Mao; et al. (Current Issues in Molecular Biology, 2023)
Silicosis is a pulmonary disease caused by the inhalation of silica. There is a lack of early and effective prevention, diagnosis, and treatment methods, and addressing silicotic fibrosis is crucial. Quercetin, a flavonoid with anti-carcinogenic, anti-inflammatory, and antiviral properties, is known to have a suppressive effect on fibrosis. The present study aimed to determine the therapeutic effect of quercetin on silicotic mice and macrophage polarity. We found that quercetin suppressed silicosis in mice. It was observed that SiO2 activated macrophage polarity and the macrophage-to-myofibroblast transition (MMT) by transforming the growth factor-β (TGF-β)-Smad2/3 signaling pathway in silicotic mice and MH-S cells. Quercetin also attenuated the MMT and the TGF-β-Smad2/3 signaling pathway in vivo and in vitro. The present study demonstrated that quercetin is a potential therapeutic agent for silicosis, which acts by regulating macrophage polarity and the MMT through the TGF-β-Smad2/3 signaling pathway.